2020
DOI: 10.1101/2020.08.07.241547
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Replay as structural inference in the hippocampal-entorhinal system

Abstract: Model-based decision making relies on the construction of an accurate representation of the underlying state-space, and localization of one’s current state within it. One way to localize is to recognize the state with which incoming sensory observations have been previously associated. Another is to update a previous state estimate given a known transition. In practice, both strategies are subject to uncertainty and must be balanced with respect to their relative confidences; robust learning requires aligning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 68 publications
1
6
0
Order By: Relevance
“…These results are in line with previous reports suggesting a role for replay when planning (Kurth-Nelson et al, 2016) and learning (Schuck & Niv, 2019) trajectories through an abstract state space in a RL problem and evidence from recordings in animals suggesting that replay can explore novel trajectories (Gupta et al, 2010;Ólafsdóttir et al, 2015). Our findings are in line with notions that generative replay provides a mechanism for efficiently learning and sampling from a generative model of the world (Foster, 2017), in line with a crucial role of replay in planning and RL (Antonov et al, 2021;Mattar & Daw, 2018) but also structure learning (Evans & Burgess, 2020). In the present study, we provide evidence for replay as a mechanism for testing hypotheses underlying compositional understanding.…”
Section: Discussionsupporting
confidence: 93%
“…These results are in line with previous reports suggesting a role for replay when planning (Kurth-Nelson et al, 2016) and learning (Schuck & Niv, 2019) trajectories through an abstract state space in a RL problem and evidence from recordings in animals suggesting that replay can explore novel trajectories (Gupta et al, 2010;Ólafsdóttir et al, 2015). Our findings are in line with notions that generative replay provides a mechanism for efficiently learning and sampling from a generative model of the world (Foster, 2017), in line with a crucial role of replay in planning and RL (Antonov et al, 2021;Mattar & Daw, 2018) but also structure learning (Evans & Burgess, 2020). In the present study, we provide evidence for replay as a mechanism for testing hypotheses underlying compositional understanding.…”
Section: Discussionsupporting
confidence: 93%
“…An interesting direction for further work involves untangling which brain areas and cognitive functions can be explained by deep (feed forward) neural networks [82], and which rely on recurrent architectures, or even richer combinations of generative structures [83]. Recurrent networks, such as RNN-S, support generative sequential sampling, reminiscent of hippocampal replay, which has been proposed as a substrate for planning, imagination, and structural inference [84, 85, 86, 87, 88].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, and with further relevance to realizing capacities for imaginative planning and creative cognition, we will attempt to include phenomena such as sharp-wave ripples and forward/reverse replay across hippocampal place fields (Ambrose et al, 2016;de la Prida, 2020;Higgins et al, 2020;Igata et al, 2020), which have been suggested to form a means of efficient structural inference over cognitive graphs (Evans and Burgess, 2020). With respect to our goal-seeking agents, forward replay may potentially help to infer (and prioritize) imagined (goal-oriented) trajectories, and reverse replay may potentially help with: (a) back-chaining from goals; (b) increasing the robustness of entailed policies via regularization, and (speculatively), and (c) allowing for a punishment mechanism via inverted orderings with respect to spike-timing-dependent-plasticity.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…If the H/E-S is the kind of gateway to high-level cognition that it is increasingly suggested to be (Evans and Burgess, 2020;George et al, 2021;McNamee et al, 2021), and if it can be well-modeled as having been selected for SLAM functionalities that were later repurposed, then we believe the difficulty of exploring the following material will more than repay the effort of attempting to make the journey. We also ask readers to note places where spatial language can be found, only some of which was intentional.…”
Section: Introductionmentioning
confidence: 99%